Wave Propagation in Biological Population Dynamics - งามสอาด, ไวพจน์ (KKU Science Journal, 2013)
The growth and dispersal of populations are the fundamental biological problems. The Fisher equation is a model that has been widely used in this system. In this article, we present the solutions of the Fisher equation that indicate the wave propagation in populations.